(untitled) (Cardiovascular Journal, 2023)
Sarcoidosis is an inflammatory granulomatous disorder of unclear etiology that can affect multiple different organ systems. Isolated cardiac sarcoidosis is very rare condition which causes lethal arrhythmia and heart failure. A definite diagnosis of cardiac sarcoidosis remains challenging. The use of multimodality imaging plays a pivotal role in the diagnosis of this entity. Cardiovasc j 2023; 15(2): 175-181